Co-Localized in Amyloid Plaques Cathepsin B as a Source of Peptide Analogs Potential Drug Candidates for Alzheimer’s Disease - Marilena K. Theodoropoulou; Konstantina D. Vraila; Nikos C. Papandreou; Georgia I. Nasi; Vassiliki A. Iconomidou (Biomolecules)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder characterized by extracellular amyloid plaques, predominantly consisting of amyloid-β (Aβ) peptides. The oligomeric form of Aβ is acknowledged as the most neurotoxic, propelling the pathological progression of AD. Interestingly, besides Aβ, other proteins are co-localized within amyloid plaques. Peptide analogs corresponding to the “aggregation-prone” regions (APRs) of these proteins could exhibit high-affinity binding to Aβ and significant inhibitory potential against the Aβ oligomerization process. The peptide analogs of co-localized protease, Cathepsin B, may act as such potent inhibitors. In silico studies on the complexes of the oligomeric state of Aβ and Cathepsin B peptide analogs were performed utilizing molecular docking and molecular dynamics simulations, revealing that these analogs disrupt the β-sheet-rich core of Aβ oligomers, a critical structural feature of their stability. Of the four peptide analogs evaluated, two demonstrated considerable potential by effectively destabilizing oligomers while maintaining low self-aggregation propensity, i.e., a crucial consideration for therapeutic safety. These findings point out the potential of APR-derived peptide analogs from co-localized proteins as innovative agents against AD, paving the way for further exploration in peptide-based therapeutic development.